Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 131 – (45 + 17) = 131 – 62 = 69
b) 71 – (58 – 33) = 71 – 25 = 46
c) (77 + 48) : 5 = 125 : 5 = 25
d) 56 : (4 x 2) = 56 : 8 = 7
a) 131 - ( 45 + 17 ) = 131 - 62 = 69
b) 71 - ( 58 - 33 ) = 71 - 25 = 46
c) ( 77 + 48 ) : 5 = 125 : 5 = 25
d) 56 : ( 4 x 2 ) = 56 : 8 = 7
a, \(\dfrac{10}{17}\) + \(\dfrac{5}{-13}\) - \(\dfrac{11}{25}\) + \(\dfrac{7}{17}\) - \(\dfrac{8}{13}\)
= ( \(\dfrac{10}{17}\) + \(\dfrac{7}{17}\)) - ( \(\dfrac{5}{13}\) + \(\dfrac{8}{13}\)) - \(\dfrac{11}{25}\)
= \(\dfrac{17}{17}\) - \(\dfrac{13}{13}\) - \(\dfrac{11}{25}\)
= 1 - 1 - \(\dfrac{11}{25}\)
= - \(\dfrac{11}{25}\)
b, 0,3 - \(\dfrac{93}{7}\) - 70% - \(\dfrac{4}{7}\)
= 0,3 - 0,7 - ( \(\dfrac{93}{7}+\dfrac{4}{7}\))
= - 0,4 - \(\dfrac{97}{7}\)
= - \(\dfrac{2}{5}\) - \(\dfrac{97}{7}\)
= - \(\dfrac{499}{35}\)
1, ( - 12 ) - ( 13 - x ) = - 15 - ( - 17 )
=> - 12 - 13 + x = - 15 + 17
=> - 25 + x = 2
=> x = 2 + 25
=> x = 27
2, 305 - x + 14 = 48 + ( x - 23 )
=> 305 - x + 14 = 48 + x - 23
=> x + x = 305 + 14 - 48 + 23
=> 2x = 294
=> x = 147
3, - ( x - 6 + 85 ) = ( x + 51 ) - 54
=> - x + 6 - 85 = x + 51 - 54
=> x + x = 6 - 85 - 51 + 54
=> 2x = - 76
=> x = - 38
4, - ( 35 - x ) - ( 37 - x ) = 33 - x
=> - 35 + x - 37 + x = 33 - x
=> x + x + x = 33 + 35 + 37
=> 3x = 105
=> x = 35
\(33,25\times48\%-33,25\times0,4+33,25\times0,02\\ =33,25\times0,48-33,25\times0,4+33,25\times0,02\\ =33,25\times\left(0,48-0,4+0,02\right)\\ =33,25\times0,1\\=3,325\)
=33,25x0,48-33,25x0,4+33,25x0,02
=33,24x(0,48-0,4+0,02)
=33,25x 0,1
=3,325
33 x ( 17 - 5 ) - 17 x ( 33 - 5 )
= 33 x 17 - 33 x 5 - 17 x 33 + 17 x 5
= ( 33 x 17 - 33 x 17 ) - 33 x 5 + 17 x 5
= 0 - 5 x ( 33 - 17 )
= -5 x 16
= -80
54 - 6 x ( 17 + 9 )
= 54 - 6 x 17 - 6 x 9
= 54 - 102 - 54
= ( 54 - 54 ) - 102
= 0 - 102 = -102
A)x+12=12+6
x=18-12
x=6
b)x-21=33-21
x=12+21
x=33
c)14-x=14-2
x=16-14
x=2
d)x-48=65-28
x=37+48
x=85
e)65-x=48+17
x=65-65
x=0
a,x+12=12+6
x+12=18
x=18-12
x=6
b, x-21=33-21
x-21=12
x=12+21
x=33
c, 14-x=14-2
14-x=12
x=14-12
x=2
d,x-48=65-28
x-48=37
x=37+48
x=85
e,65-x=48+17
65-x =65
x=65-65
x=0
a) \(=\left(\left(-\frac{1}{4}-\frac{5}{3}\right)+\frac{7}{33}\right)-\left(-\frac{15}{12}+\frac{6}{11}-\frac{48}{49}\right)\)
\(=\left(-\frac{23}{12}+\frac{7}{33}\right)+\frac{15}{12}-\frac{6}{11}+\frac{48}{49}\)
\(=\left(-\frac{23}{12}+\frac{15}{12}\right)+\left(\frac{9}{33}-\frac{6}{11}\right)+\frac{48}{49}\)
\(=-\frac{2}{3}-\frac{3}{11}+\frac{48}{49}\)
\(=\frac{65}{1617}\)
b) \(=\frac{11}{125}+\left(-\frac{17}{18}+\frac{4}{9}\right)+\left(-\frac{5}{7}+\frac{17}{14}\right)\)
\(=\frac{11}{125}-\frac{1}{2}+\frac{1}{2}\)
\(=\frac{11}{125}\)
TRẢ LỜI :
48 : x = 33 - 17
48 : x = 16
x = 48 : 16
x = 3
HỌC TỐT !
Nhớ k cho mik nha .
'/|"\\\/
'
'.\'/\>;'/;'/\\\\\\\\\\\\\\\\\\\\\\\\\\\\\/;"